2006
DOI: 10.1039/b603758p
|View full text |Cite
|
Sign up to set email alerts
|

From miso, sak? and shoyu to cosmetics: a century of science for kojic acid

Abstract: This article reviews the curious history of kojic acid, discovered as a fungal natural product in 1907. It was one of the first secondary metabolites to have its biosynthetic pathway studied by the isotope tracer technique, and, more recently, has been of interest as a skin lightening agent. There are 112 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(91 citation statements)
references
References 113 publications
1
79
0
1
Order By: Relevance
“…Data presented in figure (6) showed that the concentration of kojic acid increased along with the increase in molasses sugar concentration and reached the maximum kojic acid (19.930 g/l) at 5 % sugar. Further increasing in sugar molasses concentration resulted in decreasing the produced kojic acid concentration.…”
Section: Effect Of Sugar Concentration On Kojic Acid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data presented in figure (6) showed that the concentration of kojic acid increased along with the increase in molasses sugar concentration and reached the maximum kojic acid (19.930 g/l) at 5 % sugar. Further increasing in sugar molasses concentration resulted in decreasing the produced kojic acid concentration.…”
Section: Effect Of Sugar Concentration On Kojic Acid Productionmentioning
confidence: 99%
“…In food industries, Kojic acid is distributed naturally in traditional Japanese food such as miso, soy sauce and sake, thus, endowing these various food types with special tastes, colours and flavours (Wood 1998). kojic acid is now used as an additive to prevent browning of food materials, and as an antioxidant (Bentley 2006, Nohynek et al 2004, Rosfarizan et al 2010, Yasunobu et al 2010 due to its inhibitory effect on polyphenol oxidase in different foods (Saruno et al 1978, Chen et al 1991. The inhibitory effect of kojic acid on polyphenol oxidase is associated to the inhibition of melanosis by interfering the uptake of oxygen required for enzymatic browning, and reduction of o-quinones to diphenols to prevent the formation of the final pigment (melanin) or the combination of the above actions (Rosfarizan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In short, all three samples were rich in fatty acids and aromats, which is listed in table 2 and few interesting molecules have been described in section below. In the sample of RaMK we identified a couple of FAs and aromatic ISSN 2166-0379 2017 compounds such as kojic acid (Bentley, 2006), which is commonly employed in cosmetics and mycotoxins; benzentriols (Kocacaliskan et al, 2006;Tomá s-Barberá n et al, 1990;Zekeya et al, 2014), barbitals (Lopez-Munoz et al, 2005) and aromatic-fatty acids, which imparts bitterness and antimicrobial properties; hence it used in traditional Indian ayurvedic medicine, especially related to gastric problems. In the RiMK, we largely observed a variety of FAs and esters along with a few aromats.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…If the specific CPM to these organisms is reconstructed, then the ortholog ID in the KEGG database should be assigned to the annotated genes of these organisms by KAAS [23]. The number of nodes in each graph; 2 Percentage of the nodes among the total nodes of the entire CPM; 3 The number of arcs in each graph; 4 The average number of arcs per node; 5 The kinds of compounds in each graph. …”
Section: Construction Of the S Cerevisiae Specific Cpmmentioning
confidence: 99%
“…Many bioactive compounds, including lead compounds for the active constituents of cosmetics and novel drugs, are produced by microbial bioprocesses [1]- [3]. For example, kojic acid, a tyrosinase inhibitor, is produced by Aspergillus oryze [4]- [6].…”
Section: Introductionmentioning
confidence: 99%